2015
DOI: 10.3389/fnbeh.2015.00289
|View full text |Cite
|
Sign up to set email alerts
|

Individual variability in behavioral flexibility predicts sign-tracking tendency

Abstract: Sign-tracking rats show heightened sensitivity to food- and drug-associated cues, which serve as strong incentives for driving reward seeking. We hypothesized that this enhanced incentive drive is accompanied by an inflexibility when incentive value changes. To examine this we tested rats in Pavlovian outcome devaluation or second-order conditioning prior to the assessment of sign-tracking tendency. To assess behavioral flexibility we trained rats to associate a light with a food outcome. After the food was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
77
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(107 citation statements)
references
References 54 publications
24
77
6
Order By: Relevance
“…This appearance of a functional dorsolateral shift in DA signaling properties may thus explain aspects of addiction as a chronically relapsing disorder; with functional changes in signaling along a dorsolateral axis within the striatum, representations of drugs and drug-associated stimuli may be encoded in a more habit-like manner and therefore more resilient against treatment. Indeed, we and others have shown that repeated drug intake biases animals toward a strong sign-tracking phenotype wherein outcome-associated stimuli take on abnormally high salience (McClory and Spear, 2014; Robinson et al, 2015; Spoelder et al, 2015; Saddoris et al, 2016b), and that sign-tracking responses are insensitive to changes in value of the associated outcome (i.e., more habit-like; Nasser et al, 2015). …”
Section: Discussionmentioning
confidence: 88%
“…This appearance of a functional dorsolateral shift in DA signaling properties may thus explain aspects of addiction as a chronically relapsing disorder; with functional changes in signaling along a dorsolateral axis within the striatum, representations of drugs and drug-associated stimuli may be encoded in a more habit-like manner and therefore more resilient against treatment. Indeed, we and others have shown that repeated drug intake biases animals toward a strong sign-tracking phenotype wherein outcome-associated stimuli take on abnormally high salience (McClory and Spear, 2014; Robinson et al, 2015; Spoelder et al, 2015; Saddoris et al, 2016b), and that sign-tracking responses are insensitive to changes in value of the associated outcome (i.e., more habit-like; Nasser et al, 2015). …”
Section: Discussionmentioning
confidence: 88%
“…Behaviorally, sign- and goal-tracking have been demonstrated to be associated with differential conditioned reinforcement (Robinson and Flagel 2009; Meyer et al 2014; Beckmann and Chow 2015), differential resistance to both omission and extinction contingencies (Beckmann and Chow 2015; Ahrens et al 2016), and differential sensitivity to reward devaluation (Nasser et al 2015; Morrison et al 2015). Sign- and goal-tracking have also been demonstrated to be associated with differential dopamine signaling, and this has been interpreted as a preferential role for dopamine signaling in incentive value attribution over reward-prediction error (Flagel et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Signtracking animals orient to the cue that predicts the subsequent reward, whereas goal-tracking animals orient to the location where the outcome is delivered. A recent behavioral study has revealed a correlation between the extent to which animals manifest sign-tracking behavior and the extent to which these animals show evidence of devaluation insensitivity in their behavior, suggesting that sign tracking may be a model-free conditioned response (Nasser et al 2015). Consistent with dopamine’s involvement in model-free Pavlovian conditioning, RPE signals in the nucleus accumbens core have been associated with sign tracking.…”
Section: Neurocomputational Substratesmentioning
confidence: 99%
“…Critically, the core criterion to distinguish habitual from goal-directed behavior in the instrumental domain is also present for conditioned Pavlovian responses: Some Pavlovian responses are more sensitive (Dayan & Berridge 2014) than others to outcome value (Nasser et al 2015). Nevertheless, Pavlovian conditioned responses are often considered to be habitual in a manner analogous to habits in the instrumental domain; this conception of Pavlovian responses gives rise to the prevalent assumption that incremental synaptic plasticity implements the acquisition of Pavlovian contingencies (Rescorla & Wagner 1972).…”
Section: Introductionmentioning
confidence: 99%